Management and land use change effects on soil carbon in China s grasslands: a synthesis - Wang, Shiping; Wilkes, Andreas; Zhang, Zhicai; Chang, Xiaofeng; Lang, Rong; Wang, Yanfen; Niu, Haishan (Elsevier, 2011)
Grasslands cover about 40% of China's land area. This paper synthesizes 133 papers from China on the impacts of land use conversion and improved management practices on soil organic carbon (SOC) in China's grasslands. The synthesis finds that overgrazing and conversion of freely grazed grassland to cropland lead to an annual average decline of 2.3 2.8% in SOC, and have caused a loss of 30 35% of total grassland SOC in China. Improved management practices may reverse the loss of SOC. Exclosure of degraded grassland from grazing and conversion of cropland to abandoned fields (i.e. natural restoration) increased carbon content by 34% and 62% on average. Carbon sequestration rates were greatest during the first 30 yr after treatments began and tended to be greatest in the top 10 cm of soil. Carbon sequestration potential was negatively related to initial carbon and nitrogen concentrations in soils. Exclosure from grazing and the conversion of cropland to abandoned fields resulted in average carbon sequestration rates of 130.4 g C m?2 yr?1 for 0 40 cm soil and 128.0 g C m?2 yr?1 for 0 30 cm soil, representing annual average increases of 5.4 6.3%. Based on our results, achievement of the national objective to exclude grazing livestock from 150 million ha of China's grasslands and to establish 30 million ha of cultivated pasture by 2020 would sequester over 0.24 Pg C yr?1, which is equivalent to about 16% of fossil fuel CO2 emissions in China in 2006.